Liquid storage material, method of making same, heating module, and aerosol-generating device

CN120788289BActive Publication Date: 2026-10-27ZHUHAI QISI INTELLIGENT MFG CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511008899.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-21
Publication Date
2026-10-27
Estimated Expiration
2045-07-21

AI Technical Summary

Technical Problem

[0004]本申请的目的在于提供一种储液材料及其制备方法、发热模块、气溶胶发生装置,旨在一定程度上解决传统储液材料导液速率与香气和口感保真度矛盾的问题

Benefits of technology

[0051]本申请第一方面提供的储液材料,在储液基材的多孔骨架表面的接枝双亲聚合物层,包括叠层设置的疏水聚合物层和亲水聚合物层,其中疏水聚合物层能够调控气溶胶生成基质中甘油等大分子的扩散;而亲水聚合物层可以形成亲水通道,促进丙二醇等小分子快速传输。通过接枝双亲聚合物层使得储液基材的多孔骨架表面形成了稳定的梯度润湿性界面,可实现不同极性不同大小的分子的选择性渗透。结合在双亲聚合物层表面的纳米孔道层包括不同孔径大小的纳米级孔道既有利于后续分子筛和量子点的负载,又能够选择性吸附不同分子量大小的甜味剂和香精成分,能够延缓甜味剂和香精的迁移,实现对甜味和香气的缓释。负载在纳米孔道层表面的分子筛,利用分子筛的选择性吸附性能够吸附甜味剂分子,调控甜味剂的迁移释放。而负载在纳米孔道层表面的量子点,可通过π-π共轭作用锚定萜烯类香气分子,增强香气锚定。因而,本申请储液材料的方案通过表面双亲聚合物层、纳米孔道层、分子筛和量子点等多层级修饰改性,在储液基材的表面形成润湿性梯度,既能够确保储液材料对气溶胶生成基质的导液速率,又能够实现对气溶胶生成基质中不同极性分子的差异传输。其中,小分子甜味剂可基于界面能垒增加迁移活化能在疏水聚合物层边缘绕流传输;大分子酯类等香精成分可基于极性匹配通过亲水区域直通和界面吸附加速渗透传输;甘油/丙二醇等气溶胶生成基质溶剂分子可在亲水聚合物层通过润湿梯度驱动快速毛细渗透传输。同时,利用分子筛选择性吸附与量子点定向锚定的协同作用,分子筛调控甜味剂缓释,量子点增强香气锚定,实现香气-甜味的分级控释,突破了传统储液材料导液速率与甜味和香气保真度的矛盾。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120788289B_ABST
    Figure CN120788289B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of liquid storage materials, and particularly relates to a liquid storage material, a preparation method thereof, a heating module and an aerosol generating device. The liquid storage material comprises a porous structure liquid storage base material, an amphiphilic polymer layer grafted on the surface of the porous framework of the liquid storage base material, a nanopore layer combined on the surface of the amphiphilic polymer layer away from the liquid storage base material, and a molecular sieve and quantum dots loaded on the surface of the nanopore layer away from the amphiphilic polymer layer; the amphiphilic polymer layer comprises a hydrophobic polymer layer and a hydrophilic polymer layer arranged in a stack. The surface of the liquid storage base material is modified in multiple layers on the surface of the porous framework, so that a wetting gradient is formed on the surface of the liquid storage base material, which can not only ensure the liquid guiding rate of the liquid storage material to the aerosol generating substrate, but also realize the differential transmission of different polar molecules in the aerosol generating substrate. The application realizes the graded control of aroma and sweetness, and breaks through the contradiction between the liquid guiding rate of the traditional liquid storage material and the sweetness and aroma fidelity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of liquid storage material technology, and particularly relates to a liquid storage material and its preparation method, a heating module, and an aerosol generating device. Background Technology

[0002] An aerosol generator is an electronic device that generates aerosols through heating. It typically includes a heating module, a power supply module, and a control module. The heating module is the core component of the aerosol generator, mainly consisting of heating elements and a storage liquid. The aerosol-generating matrix stored in the storage liquid is heated by the heating elements to form an aerosol that can be inhaled by the user. Therefore, the liquid-conducting ability of the storage liquid to the aerosol-generating matrix has a significant impact on the effectiveness of the aerosol generator.

[0003] There is a trade-off between the liquid conduction rate of traditional storage materials and the preservation of aroma and taste. At high liquid conduction rates, the aerosol-generating matrix flows rapidly, and sweet and aroma components in the matrix are quickly carried away. Sweet and flavor molecules are not fully adsorbed into the storage material, resulting in a concentrated release and an excessively high concentration of sweet and flavor components in the aerosol. This makes the aerosol taste overly sweet, with unclear aroma layers, failing to create a distinct top, middle, and base note release effect, thus affecting the user experience and leading to incomplete sweetness and aroma release. Conversely, at low liquid conduction rates, sweetness and flavor are well retained, but aerosol generation efficiency decreases, easily resulting in a dry aerosol taste or insufficient aerosol quantity, also affecting the user experience. Summary of the Invention

[0004] The purpose of this application is to provide a liquid storage material and its preparation method, a heating module, and an aerosol generating device, which aims to solve, to some extent, the contradiction between the liquid conduction rate and the authenticity of aroma and taste of traditional liquid storage materials.

[0005] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows: In a first aspect, this application provides a liquid storage material, comprising a porous liquid storage substrate, an amphiphilic polymer layer grafted onto the porous framework surface of the liquid storage substrate, a nanoporous layer bonded to the surface of the amphiphilic polymer layer opposite to the liquid storage substrate, and molecular sieves and quantum dots loaded on the surface of the nanoporous layer opposite to the amphiphilic polymer layer; wherein the amphiphilic polymer layer comprises a hydrophobic polymer layer and a hydrophilic polymer layer stacked together.

[0006] In some possible implementations, the nanoporous layer includes a porous nanoframework material and inorganic nanoparticles bonded to the porous nanoframework material.

[0007] In some possible implementations, along the direction from the liquid storage substrate to the amphiphilic polymer layer, the amphiphilic polymer layer comprises a plurality of alternating layers of hydrophobic polymer layers and hydrophilic polymer layers, wherein one of the hydrophobic polymer layers is bonded to the porous skeleton surface of the liquid storage substrate.

[0008] In some possible implementations, along the direction from the liquid storage substrate to the amphiphilic polymer layer, the amphiphilic polymer layer sequentially includes a first hydrophobic polymer layer, a first hydrophilic polymer layer, a second hydrophobic polymer layer, and a second hydrophilic polymer layer.

[0009] In some possible implementations, the thicknesses of the first hydrophobic polymer layer and the second hydrophobic polymer layer in the amphiphilic polymer layer are independently 20 nm to 30 nm.

[0010] In some possible implementations, the thicknesses of the first hydrophilic polymer layer and the second hydrophilic polymer layer in the amphiphilic polymer layer are independently 10 nm to 20 nm.

[0011] In some possible implementations, the interlayer spacing between the first hydrophobic polymer layer and the first hydrophilic polymer layer, the first hydrophilic polymer layer and the second hydrophobic polymer layer, and the second hydrophobic polymer layer and the second hydrophilic polymer layer are each independently 10 nm to 50 nm.

[0012] In some possible implementations, the hydrophobic polymer layer includes at least one hydrophobic polymer selected from perfluorohexyl ethyl acrylate, polydimethylsiloxane, polytetrafluoroethylene derivatives, and polydodecyl acrylate.

[0013] In some possible implementations, the hydrophilic polymer layer includes at least one hydrophilic polymer selected from polyethylene glycol methacrylate, polyvinyl alcohol, polyvinylpyrrolidone, and polyacrylic acid.

[0014] In some possible implementations, the amount of hydrophobic polymer grafted into the amphiphilic polymer layer is 1.2 μg / cm³. 2 ~2.5μg / cm 2 .

[0015] In some possible implementations, the amount of hydrophilic polymer grafted into the amphiphilic polymer layer is 1.8 μg / cm³. 2 ~3.0μg / cm 2 .

[0016] In some possible implementations, the mass ratio of the grafted hydrophilic polymer to the hydrophobic polymer in the amphiphilic polymer layer is 1:(1~1.5).

[0017] In some possible implementations, the thickness of the nanoporous layer is 200 nm to 500 nm.

[0018] In some possible implementations, the inorganic nanoparticles include at least one of SiO2 nanoparticles, TiO2 nanoparticles, and Al2O3 nanoparticles.

[0019] In some possible implementations, the average particle size of the inorganic nanoparticles is 10 nm to 30 nm.

[0020] In some possible implementations, the porous nanoframework material includes at least one of nanofiber materials, metal-organic frameworks, graphene oxide, and carbon nanotubes.

[0021] In some possible implementations, the nanofiber material includes at least one of chitin nanofibers and cellulose nanocrystals.

[0022] In some possible implementations, the porous nanoframework material includes the nanofiber material, in which case the nanofiber material forms a three-dimensional network framework in the nanopore layer, and the inorganic nanoparticles are loaded in the three-dimensional network framework.

[0023] In some possible implementations, the nanoporous layer also has a coupling structure.

[0024] In some possible implementations, the nanoporous layer includes macropores of 50 nm to 200 nm formed by the three-dimensional network framework, mesopores of 10 nm to 50 nm formed by the stacking of inorganic nanoparticles, and micropores of 0.5 nm to 1.2 nm inside the nanofiber material crystal.

[0025] In some possible implementations, the porosity of the nanoporous layer is 60% to 75%.

[0026] In some possible implementations, the molecular sieve includes at least one of ZSM-5 molecular sieve, Ga-ZSM-5 molecular sieve, and Sn-ZSM-5 molecular sieve; In some possible implementations, the average particle size of the molecular sieve is 200 nm to 300 nm.

[0027] In some possible implementations, the average pore size of the molecular sieve is 0.5 nm to 2 nm.

[0028] In some possible implementations, the molecular sieve is loaded into the liquid storage material at a rate of 2 wt% to 3 wt%.

[0029] In some possible implementations, the quantum dot loading in the reservoir material is 0.5 wt% to 1.5 wt%. In some possible implementations, the quantum dots include at least one of nitrogen-doped carbon quantum dots, chitosan-cyclodextrin composite quantum dots, metal-organic framework modified quantum dots, and citric acid-polyetherimide quantum dots.

[0030] In some possible implementations, the nitrogen doping mass percentage of the nitrogen element in the nitrogen-doped carbon quantum dots is 6% to 9%.

[0031] Secondly, this application provides a method for preparing a liquid storage material, comprising the following steps: Obtaining a porous liquid storage substrate; An amphiphilic polymer layer is prepared on the porous framework surface of the liquid storage substrate; the amphiphilic polymer layer comprises a hydrophobic polymer layer and a hydrophilic polymer layer stacked together. A nanoporous layer is prepared on the surface of the amphiphilic polymer layer; Molecular sieves and quantum dots are loaded onto the surface of the nanoporous layer to obtain a liquid storage material.

[0032] In some possible implementations, the step of preparing the amphiphilic polymer layer includes: After plasma activation treatment of the liquid storage substrate, an activated substrate is obtained; The activated substrate is immersed in a solution of hydrophobic polymer monomers and subjected to a plasma hydrophobic grafting reaction to form a first hydrophobic polymer layer. The polymer is immersed in a solution of hydrophilic polymer monomers and subjected to a plasma hydrophilic grafting reaction to form a first hydrophilic polymer layer. On the surface of the first hydrophilic polymer layer, a second hydrophobic polymer layer and a second hydrophilic polymer layer are sequentially stacked to obtain the amphiphilic polymer layer.

[0033] In some possible implementations, the plasma activation treatment has a power of 40W to 60W, a duration of 90s to 150s, and a temperature of 30℃ to 50℃.

[0034] In some possible implementations, the concentration of the hydrophobic polymer monomer solution is 20% to 40%.

[0035] In some possible implementations, the concentration of the hydrophilic polymer monomer solution is 10% to 30%.

[0036] In some possible implementations, the power of the plasma hydrophobic grafting reaction is 20W~40W, and the duration is 20s~60s.

[0037] In some possible implementations, the power of the plasma hydrophilic grafting reaction is 10W~30W, and the duration is 10s~60s.

[0038] In some possible implementations, the nanoporous layer comprises a porous nanoframework material and inorganic nanoparticles bonded to the porous nanoframework material, and the steps for preparing the nanoporous layer include: The inorganic nanoparticle precursor material and the porous nanoframework material are dissolved in a solvent and subjected to hydrolysis and condensation reactions to obtain a sol. The sol is deposited onto the surface of the amphiphilic polymer layer to form the nanoporous layer; The surface of the nanoporous layer is treated with a coupling agent solution and then annealed to form a coupling structure in the nanoporous layer.

[0039] In some possible implementations, the precursor material includes at least one of tetraethyl orthosilicate, methyltrimethoxysilane, sodium silicate, tetramethylsilane, bio-derived silicon source, organic-inorganic hybrid precursor, and 3-aminopropyltriethoxysilane.

[0040] In some possible implementations, the mass ratio of the precursor material to the porous nanoframework material is (4~6):1.

[0041] In some possible implementations, the pH value of the mixed solution of the precursor material, the porous nanoframework material, and the solvent is 4 to 5.

[0042] In some possible implementations, the coupling agent includes at least one of 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, mercaptosilane, epoxysilane, titanate coupling agent, and polydopamine.

[0043] In some possible implementations, the concentration of the coupling agent solution is 2% to 4%.

[0044] In some possible implementations, the annealing process is carried out at a temperature of 70°C to 90°C for a duration of 0.5 h to 2 h.

[0045] In some possible implementations, the loading of the molecular sieve includes the steps of: immersing a substrate on which the nanoporous layer is formed on its surface in a dispersion of the molecular sieve, and loading the molecular sieve onto the surface of the nanoporous layer by vacuum impregnation.

[0046] In some possible implementations, loading the quantum dots includes the steps of: immersing a substrate on which the nanoporous layer is formed on its surface in a dispersion of the quantum dots, wherein the quantum dots are loaded onto the surface of the nanoporous layer through conjugation.

[0047] In some possible implementations, the vacuum degree of the vacuum impregnation is no higher than 10. -3 Pa, duration is 1h~3h.

[0048] In some possible implementations, the molecular sieve is loaded onto the surface of the nanoporous layer before the quantum dots are loaded.

[0049] Thirdly, this application provides a heating module, including the above-described liquid storage material and / or the liquid storage material prepared by the above method.

[0050] Fourthly, this application provides an aerosol generating device, including a power supply assembly and the aforementioned heating module.

[0051] The liquid storage material provided in the first aspect of this application comprises a grafted amphiphilic polymer layer on the porous framework surface of the liquid storage substrate. This layer includes a stacked hydrophobic polymer layer and a hydrophilic polymer layer. The hydrophobic polymer layer can regulate the diffusion of macromolecules such as glycerol in the aerosol-generating matrix, while the hydrophilic polymer layer can form hydrophilic channels to promote the rapid transport of small molecules such as propylene glycol. The grafted amphiphilic polymer layer creates a stable gradient wettability interface on the porous framework surface of the liquid storage substrate, enabling selective permeation of molecules of different polarities and sizes. The nanoporous layer attached to the surface of the amphiphilic polymer layer, including nanoscale pores of varying sizes, is beneficial for subsequent loading of molecular sieves and quantum dots, and can selectively adsorb sweeteners and flavorings of different molecular weights, thus delaying their migration and achieving sustained release of sweetness and aroma. The molecular sieve loaded on the surface of the nanoporous layer utilizes its selective adsorption properties to adsorb sweetener molecules, regulating their migration and release. Quantum dots loaded on the surface of the nanoporous layer can anchor terpene aroma molecules through π-π conjugation, enhancing aroma anchoring. Therefore, the liquid storage material solution of this application, through multi-level modification including a surface amphiphilic polymer layer, nanoporous layer, molecular sieve, and quantum dots, forms a wettability gradient on the surface of the liquid storage substrate. This ensures both the liquid conduction rate of the liquid storage material to the aerosol-generating matrix and the differential transport of molecules of different polarities within the aerosol-generating matrix. Specifically, small-molecule sweeteners can increase their migration activation energy based on interfacial energy barriers, allowing for flow transport around the edges of the hydrophobic polymer layer; large-molecule esters and other fragrance components can accelerate permeation transport through direct hydrophilic region flow and interfacial adsorption based on polarity matching; and solvent molecules of the aerosol-generating matrix, such as glycerol / propylene glycol, can be rapidly transported through capillary permeation driven by the wettability gradient in the hydrophilic polymer layer. Meanwhile, by utilizing the synergistic effect of selective adsorption by molecular sieves and directional anchoring by quantum dots, molecular sieves regulate the sustained release of sweeteners, while quantum dots enhance aroma anchoring, thereby achieving graded controlled release of aroma and sweetness, breaking through the contradiction between the liquid conduction rate and the preservation of sweetness and aroma in traditional liquid storage materials.

[0052] The second aspect of this application describes a method for preparing a liquid storage material. An amphiphilic polymer layer is prepared on the surface of a liquid storage substrate. Grafting the amphiphilic polymer layer creates a stable gradient wettability interface on the porous framework surface of the liquid storage substrate, enabling selective permeation of molecules of different polarities and sizes. A nanoporous layer is prepared on the surface of the amphiphilic polymer layer. The resulting nanoscale pores facilitate the subsequent loading of molecular sieves and quantum dots, and can selectively adsorb sweeteners and flavorings of different molecular weights, thus delaying their migration and achieving sustained release of sweetness and aroma. Molecular sieves and quantum dots are loaded onto the surface of the nanoporous layer. The selective adsorption of molecular sieves adsorbs sweetener molecules, regulating their migration and release. The π-π conjugation of quantum dots anchors terpene aroma molecules, enhancing aroma anchoring. This ensures that the prepared liquid storage material can both guarantee the liquid conduction rate to the aerosol-generating matrix and achieve differential transport of molecules of different polarities within the aerosol-generating matrix, realizing graded controlled release of aroma and sweetness.

[0053] The third aspect of this application concerns a heating module, including the aforementioned liquid storage material. Through multi-level modification using a surface amphiphilic polymer layer, a nanoporous layer, molecular sieves, and quantum dots, the material ensures both the liquid conduction rate to the aerosol-generating matrix and the differential transport of molecules of different polarities within the aerosol-generating matrix. This enables the heating module to achieve graded controlled release of aroma and sweetness, overcoming the contradiction between the liquid conduction rate of the storage material and the fidelity of sweetness and aroma in traditional heating modules.

[0054] The aerosol generating device of the fourth aspect of this application includes a power supply component and the aforementioned heating module. This heating module can achieve graded controlled release of aroma and sweetness, overcoming the contradiction between the liquid conduction rate of the storage material and the fidelity of sweetness and aroma in traditional heating modules. Therefore, it can improve the user experience of the aerosol generating device. Attached Figure Description

[0055] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0056] Figure 1 This is a schematic diagram of the structure of the liquid storage material provided in the embodiments of this application; Figure 2 This is a schematic flowchart of the preparation method of the liquid storage material provided in the embodiments of this application. Detailed Implementation

[0057] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0058] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.

[0059] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0060] It should be understood that in the various embodiments of this application, the order of the above processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0061] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms "a" and "the" as used in the embodiments of this application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0062] The weights of the relevant components mentioned in the embodiments of this application can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this application is within the scope disclosed in the embodiments of this application. Specifically, the mass described in the embodiments of this application can be a mass unit known in the chemical industry, such as µg, mg, g, or kg.

[0063] The terms "first" and "second" are used for descriptive purposes only, to distinguish objects, such as substances, from one another, and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. For example, without departing from the scope of the embodiments of this application, "first XX" may also be referred to as "second XX," and similarly, "second XX" may also be referred to as "first XX." Thus, features defined with "first" and "second" may explicitly or implicitly include one or more of that feature.

[0064] The first aspect of this application provides a liquid storage material, including a porous liquid storage substrate, an amphiphilic polymer layer grafted onto the porous framework surface of the liquid storage substrate, a nanoporous layer bonded to the surface of the amphiphilic polymer layer away from the liquid storage substrate, and molecular sieves and quantum dots loaded on the surface of the nanoporous layer away from the amphiphilic polymer layer; wherein the amphiphilic polymer layer includes a hydrophobic polymer layer and a hydrophilic polymer layer stacked together.

[0065] The liquid storage material provided in the first aspect of this application comprises a grafted amphiphilic polymer layer on the porous framework surface of the liquid storage substrate. This layer includes a stacked hydrophobic polymer layer and a hydrophilic polymer layer. The hydrophobic polymer layer can regulate the diffusion of macromolecules such as glycerol in the aerosol-generating matrix, while the hydrophilic polymer layer can form hydrophilic channels to promote the rapid transport of small molecules such as propylene glycol. The grafted amphiphilic polymer layer creates a stable gradient wettability interface on the surface of the liquid storage substrate, enabling selective permeation of molecules of different polarities and sizes. The nanoporous layer attached to the surface of the amphiphilic polymer layer includes nanoscale pores of varying sizes, which facilitates the loading of molecular sieves and quantum dots and allows for the selective adsorption of sweeteners and flavorings of different molecular weights. This delays the migration of sweeteners and flavorings, achieving a sustained release of sweetness and aroma. The molecular sieve loaded on the surface of the nanoporous layer utilizes its selective adsorption properties to adsorb sweetener molecules, regulating the migration and release of sweeteners. Quantum dots loaded on the surface of the nanoporous layer can anchor terpene aroma molecules through π-π conjugation, enhancing aroma anchoring. Therefore, the liquid storage material solution of this application, through multi-level modification including a surface amphiphilic polymer layer, nanoporous layer, molecular sieve, and quantum dots, forms a wettability gradient on the surface of the liquid storage substrate. This ensures both the liquid conduction rate of the liquid storage material to the aerosol-generating matrix and the differential transport of molecules of different polarities within the aerosol-generating matrix. Specifically, small-molecule sweeteners can increase their migration activation energy based on interfacial energy barriers, allowing for flow transport around the edges of the hydrophobic polymer layer; large-molecule esters and other fragrance components can accelerate permeation transport through direct hydrophilic region flow and interfacial adsorption based on polarity matching; and solvent molecules of the aerosol-generating matrix, such as glycerol / propylene glycol, can be rapidly transported through capillary permeation driven by the wettability gradient in the hydrophilic polymer layer. Meanwhile, by utilizing the synergistic effect of selective adsorption by molecular sieves and directional anchoring by quantum dots, molecular sieves regulate the sustained release of sweeteners, while quantum dots enhance aroma anchoring, thereby achieving graded controlled release of aroma and sweetness, breaking through the contradiction between the liquid conduction rate and the preservation of sweetness and aroma in traditional liquid storage materials.

[0066] In some possible implementations, the amphiphilic polymer layer comprises multiple alternating layers of hydrophobic and hydrophilic polymers, with one hydrophobic polymer bonded to the porous framework surface of the liquid storage substrate. The alternating layers of hydrophobic and hydrophilic polymers create a gradient wettability interface on the surface of the liquid storage substrate, enabling selective permeation and diffusion regulation of molecules of different polarities and sizes in the aerosol generation matrix through synergistic effects.

[0067] In some possible implementations, along the direction from the liquid storage substrate to the amphiphilic polymer layer, the amphiphilic polymer layer sequentially comprises a first hydrophobic polymer layer, a first hydrophilic polymer layer, a second hydrophobic polymer layer, and a second hydrophilic polymer layer. In this case, the multiple alternating layers of hydrophobic and hydrophilic polymers create a stable gradient wettability interface on the surface of the liquid storage substrate, enabling selective penetration and diffusion regulation of molecules of different polarities and sizes in the aerosol generation matrix through synergistic effects. Specifically, the ultra-low surface energy and rigid structure of the hydrophobic polymer layer can regulate the diffusion of macromolecules such as glycerol in the aerosol generation matrix; the hydrophilic polymer layer, after absorbing water and swelling, constructs hydrophilic channels, promoting the rapid transport of small molecules such as propylene glycol. The alternating grafting of these two layers forms a layered structure with microphase separation. This "microphase separation," composed of alternating grafted amphiphilic polymer layers, can also be understood as layered phase separation. The hydrophobic polymer layer acts as a molecular barrier, hindering the penetration of macromolecules, while the hydrophilic polymer layer acts as a rapid diffusion channel, accelerating the migration of small molecules. During dynamic swelling, the hydrophilic polymer absorbs water, increasing its interchain spacing to form a "highway," while the hydrophobic polymer maintains a stable structure within the aerosol-forming matrix, inhibiting macromolecular permeation through size exclusion and capillary resistance. Ultimately, small-molecule sweeteners diffuse faster due to the free diffusion mechanism of the hydrophilic polymer layer, while macromolecular flavors have limited diffusion due to the strong interactions of the hydrophobic polymer layer, achieving flavor migration inhibition and orderly sweetener release. This design, through the construction of a biomimetic layered heterostructure, improves liquid conductivity while utilizing interfacial chemical potential differences to achieve orderly release of flavor molecules, thus solving the aroma mixing problem caused by traditional high liquid conductivity materials.

[0068] In some possible implementations, the hydrophobic polymer layer includes at least one hydrophobic polymer selected from perfluorohexyl ethyl acrylate, polydimethylsiloxane, polytetrafluoroethylene derivatives, and polydodecyl acrylate. These hydrophobic polymers can all regulate the diffusion of macromolecules such as glycerol and fragrances in the aerosol-generating matrix.

[0069] In some possible implementations, the hydrophobic polymer layer includes polyperfluorohexyl ethyl acrylate (PFHEA). The hydrophobicity of PFHEA is mainly reflected in two aspects: First, its molecular structure characteristics. The main chain contains perfluorohexyl ethyl acrylate, the side chains have low polarity of the CF bonds, resulting in extremely low surface energy. Furthermore, the tightly helical arrangement of the fluorocarbon chains forms a dense hydrophobic barrier. The symmetrical distribution of the CF bond electron clouds makes it difficult for them to interact with polar molecules (such as water and glycerol) in a dipole manner. Simultaneously, the rigid structure of the fluorocarbon chains forms a molecular-level barrier, preventing the penetration of polar molecules (such as the sweetener ethyl maltol). Second, its surface physicochemical properties. PFHEA forms a nanoscale rough structure on the surface of the substrate fibers, trapping air in the micropores. The low surface energy makes it difficult for polar liquids (such as propylene glycol in the aerosol-generating matrix) to wet the surface, increasing the resistance to contact line movement, thus exhibiting excellent hydrophobicity.

[0070] In some possible implementations, the hydrophilic polymer layer includes at least one hydrophilic polymer selected from polyethylene glycol methacrylate, polyvinyl alcohol, polyvinylpyrrolidone, and polyacrylic acid; these hydrophilic polymers can all form hydrophilic channels to promote the rapid transport of small molecules such as propylene glycol and sweeteners.

[0071] In some possible implementations, the hydrophilic polymer layer includes polyethylene glycol methacrylate (PEGMA). The hydrophilicity of PEGMA stems from its molecular structure and physicochemical properties. The ether bonds (-O-) in its main chain act as strong hydrogen bond acceptors, forming hydrogen bonds with water molecules. Simultaneously, the PEG chain exhibits high flexibility and a large degree of rotational freedom, facilitating the adsorption of polar molecules. Furthermore, each ethylene oxide (EO) unit can bind 2-3 water molecules, forming a hydrated layer approximately 1 nm to 2 nm thick, significantly enhancing hydrophilicity. PEGMA can also reduce the surface tension of liquids, increasing the capillary rise rate of the aerosol-generating matrix (such as a propylene glycol / glycerol mixture) between fibers through capillary effects, further strengthening its hydrophilicity.

[0072] In some possible implementations, the hydrophobic polymer layer includes polyperfluorohexyl ethyl acrylate (PFHEA), and the hydrophilic polymer layer includes polyethylene glycol methacrylate (PEGMA). PFHEA and PEGMA work synergistically to regulate molecular diffusion: PFHEA, with its ultra-low surface energy and rigid structure of the perfluorohexyl segments, forms strongly hydrophobic microdomains that interact hydrophobically with macromolecules such as flavorings and glycerin, restricting their diffusion; PEGMA, through its ethylene glycol units, forms a hydrogen bond network with water molecules, and after absorbing water and swelling, constructs hydrophilic channels, promoting the rapid diffusion of small molecules such as sweeteners and propylene glycol. The alternating grafting of these two layers forms a microphase-separated layered structure (interlayer spacing 10–50 nm). The PFHEA layer acts as a molecular barrier to hinder the penetration of macromolecules, while the PEGMA layer acts as a rapid diffusion channel to accelerate the migration of small molecules. This allows small-molecule sweeteners to diffuse faster due to the free diffusion mechanism of the hydrophilic regions, while the diffusion of macromolecule flavorings is restricted due to the strong interactions of the hydrophobic regions, achieving flavor migration inhibition and orderly release of sweeteners.

[0073] In some possible implementations, the thicknesses of the first and second hydrophobic polymer layers in the amphiphilic polymer layer are independently 20 nm to 30 nm, meaning the thickness of a single hydrophobic polymer layer is 20 nm to 30 nm. Exemplary examples include typical but not limiting values ​​such as 20 nm, 21 nm, 22 nm, 23 nm, 24 nm, 25 nm, 26 nm, 27 nm, 28 nm, 29 nm, and 30 nm, or any range between any two values. This thickness ensures that the hydrophobic polymer layer can regulate the diffusion of macromolecules such as glycerol and fragrances in the aerosol-generating matrix.

[0074] In some possible implementations, the thicknesses of the first and second hydrophilic polymer layers in the amphiphilic polymer layer are independently 10 nm to 20 nm, meaning the thickness of a single hydrophilic polymer layer is 10 nm to 20 nm. Exemplary examples include any typical but non-limiting point value or a range between any two points, such as 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, and 20 nm. This thickness ensures rapid transport of small molecules such as propylene glycol and sweeteners by the hydrophilic polymer layer.

[0075] In some possible implementations, the interlayer spacing between the first hydrophobic polymer layer and the first hydrophilic polymer layer, the first hydrophilic polymer layer and the second hydrophobic polymer layer, and the second hydrophobic polymer layer and the second hydrophilic polymer layer are each independently 10 nm to 50 nm, meaning that there is an interlayer spacing of 10 nm to 50 nm between adjacent individual hydrophobic polymer layers and individual hydrophilic polymer layers. For example, the interlayer spacing can be any typical but non-limiting point value such as 10 nm, 20 nm, 30 nm, 40 nm, or 50 nm, or a range between any two point values. In this case, a transition channel is formed at the phase boundary between the hydrophobic polymer layer and the hydrophilic polymer layer. The interfacial energy barrier can increase the migration activation energy of small molecules. By grafting the amphiphilic polymer layer, a stable gradient wettability interface is formed on the surface of the liquid storage substrate, which can better achieve selective penetration of molecules of different polarities and sizes.

[0076] In some possible implementations, the grafting amount of the hydrophobic polymer in the amphiphilic polymer layer is 1.2 μg / cm. 2 ~2.5μg / cm 2 For example, it could be 1.2 μg / cm³. 2 1.3 μg / cm 2 1.5 μg / cm 2 1.8 μg / cm 2 2.0 μg / cm 2 2.2 μg / cm 2 2.5 μg / cm 2 Typical but not limiting point values ​​or intervals between any two point values. In this case, it is ensured that the hydrophobic polymer layer can regulate the diffusion of macromolecules such as glycerol and fragrances in the aerosol-generating matrix.

[0077] In some possible implementations, the grafting amount of the hydrophilic polymer in the amphiphilic polymer layer is 1.8 μg / cm. 2 ~3.0μg / cm 2 For example, it could be 1.8 μg / cm³. 22.0 μg / cm 2 2.2 μg / cm 2 2.5 μg / cm 2 2.8 μg / cm 2 3.0 μg / cm 2 Typical but not limiting point values ​​or intervals between any two point values. In this case, ensure the rapid transport of small molecules such as propylene glycol and sweeteners by the hydrophilic polymer layer.

[0078] In some possible implementations, the mass ratio of the grafted hydrophilic polymer to the hydrophobic polymer in the amphiphilic polymer layer is 1:(1~1.5). Exemplary examples include typical but not limiting values ​​such as 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, and 1:1.5, or any range between any two values. In this case, it is beneficial to ensure the synergistic effect of the hydrophobic and hydrophilic polymer layers, resulting in a stable gradient wettability interface on the surface of the liquid reservoir substrate, enabling selective penetration of molecules of different polarities and sizes.

[0079] For example, in the amphiphilic polymer layer of this application embodiment, the amount of grafting of hydrophilic polymer and hydrophobic polymer can be calculated by measuring the mass change of the substrate before and after grafting, and the amount of grafting per unit mass or per unit surface area can be calculated.

[0080] In some possible implementations, the nanoporous layer includes porous nanoframework materials and inorganic nanoparticles bonded to the porous nanoframework materials; through the combined action of the porous nanoframework materials and inorganic nanoparticles, nanoscale channels of different pore sizes are formed, which is beneficial for both the loading of molecular sieves and quantum dots and the slow release of sweetness and aroma.

[0081] In some possible implementations, the thickness of the nanoporous layer is 200 nm to 500 nm; exemplaryly, the thickness can be any typical but non-limiting value such as 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, or 500 nm, or a range between any two values. In this case, it ensures that the nanoporous layer can selectively adsorb sweeteners and flavorings of different molecular weights, achieving a sustained release of sweetness and aroma. It also facilitates the subsequent loading of molecular sieves and quantum dots, better enabling graded control of sweetness and aroma release.

[0082] In some possible implementations, inorganic nanoparticles include at least one of SiO2 nanoparticles, TiO2 nanoparticles, and Al2O3 nanoparticles; these inorganic nanoparticles can enhance the surface hardness of the nanoporous layer, and nanoporous structures can be formed between the inorganic nanoparticles to produce a molecular sieve effect, which can confine small molecule sweeteners or small molecule flavors, and realize the gradient release of sweetener and flavor molecules.

[0083] In some possible implementations, the average particle size of the inorganic nanoparticles is 10 nm to 30 nm; for example, the average particle size of the inorganic nanoparticles can be any typical but non-limiting point value or a range between any two points, such as 10 nm, 15 nm, 20 nm, 25 nm, or 30 nm. In this case, the inorganic nanoparticles are loaded into porous nanoframework materials, and mesopores of several nanometers can be formed between the inorganic nanoparticles, allowing small molecules to pass through while blocking large molecules, thus constructing sieving channels.

[0084] Among some possible implementations, porous nanoframework materials include at least one of nanofibers, metal-organic frameworks, graphene oxide, and carbon nanotubes. These materials can all provide porous nanoframeworks for loading inorganic nanoparticles. Metal-organic frameworks possess their own framework structure, while two-dimensional wires or sheets such as nanofibers, graphene oxide, and carbon nanotubes can form three-dimensional network structures, which is beneficial for loading inorganic nanoparticles. Furthermore, the formed porous structure can selectively adsorb sweeteners and flavorings of different molecular weights, achieving a sustained release of sweetness and aroma.

[0085] In some possible implementations, nanofiber materials include at least one of chitin nanofibers and cellulose nanocrystals. These nanofiber materials also possess a 0.5 nm to 2 nm internal structure, which can selectively delay the release of small molecules.

[0086] In some possible implementations, the porous nanoframework material includes nanofiber materials, in which the nanofiber material forms a three-dimensional network framework in the nanopore layer, and inorganic nanoparticles are loaded in the three-dimensional network framework.

[0087] In some possible implementations, the nanoporous layer includes macropores (50nm-200nm) formed by a three-dimensional network framework, mesopores (10nm-50nm) formed by the stacking of inorganic nanoparticles, and micropores (0.5nm-1.2nm) within the nanofiber crystals. In this case, the nanoporous layer possesses a three-tiered pore size structure. Through the molecular sieve effect, pores of different sizes can selectively adsorb sweeteners and flavorings of different molecular weights, thus delaying their migration and achieving graded release and control of sweetness and aroma. This hierarchical structure achieves directional sieving and efficient transport of sweetener and flavoring molecules through pore size differences. Specifically, micropores selectively capture sweeteners; mesopores block sweeteners while allowing flavorings to pass through, regulating the permeation rate of polar molecules; and macropores ensure liquid flux.

[0088] In some possible implementations, the organic-inorganic hybrid nanostructure in the nanoporous layer is constructed with cellulose nanocrystals (CNC) and SiO2 nanoparticles as its core. The CNC, with its high aspect ratio and rigid rod-like structure, forms a three-dimensional network framework (pore size 20~100nm) through hydrogen bonding and physical entanglement of surface hydroxyl groups. At the same time, SiO2 nanoparticles (average particle size 10nm~30nm) are combined with the CNC through chemical bonding (Si-OC covalent bonds) and physical coating (generating a "CNC core-SiO2 shell" structure and filling the network gaps) to form an interpenetrating structure. The CNC network provides mechanical support and enhances the toughness of the nanoporous layer, while the SiO2 nanoparticles increase surface hardness, and the interfacial chemical cross-linking points inhibit particle aggregation. This structure exhibits a multi-level pore structure, including macropores of 50nm~200nm formed by the gaps between CNC networks, mesopores of 2nm~5nm generated by SiO2 accumulation, and micropores of 0.5nm~1.2nm inside the CNC crystal. Through molecular sieve effect (preferential adsorption of flavor esters with molecular weight >300Da), electrostatic double layer repulsion (inhibiting sweetener migration), and gradient pore design, it achieves the directional regulation and sustained release function of flavor molecules.

[0089] In some possible implementations, the nanoporous layer also incorporates coupling structures. These coupling structures further enhance the bonding stability between the inorganic nanoparticles and the porous nanoframework material within the nanoporous layer, and also strengthen the bond between the nanoporous layer and the substrate. This also facilitates the subsequent loading of molecular sieves and quantum dots.

[0090] In some possible implementations, the porosity of the nanoporous layer is 60%–75%. Exemplary examples include typical but not limiting values ​​such as 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, and 75%, or any range between any two values. In this case, the varying porosity of the nanoporous layer sufficiently ensures the hierarchical release and control of molecules of different sizes within the aerosol-generating matrix.

[0091] For example, in the nanoporous layer of this application embodiment, the porosity can be calculated by measuring the dry mass (dried to constant weight), apparent volume (obtained by water displacement method, caliper measurement or three-dimensional scanning) and true density (by true density meter or helium displacement method, i.e., the density of the material when there are no pores).

[0092] In some possible implementations, the molecular sieve includes at least one of ZSM-5, Ga-ZSM-5, and Sn-ZSM-5 molecular sieves. These molecular sieves possess pores of approximately 0.55 nm, enabling selective confinement of sweetener molecules, while their surface acidic sites catalyze the orderly release of ester flavor molecules, thus achieving functional binding. The binding mechanism between these molecular sieves and the nanoporous layer surface is primarily physical adsorption, such as hydrogen bonding. The molecular sieves achieve binding through surface pore anchoring (embedding themselves into micron-sized pores or interfiber gaps on the nanoporous layer surface). Furthermore, the molecular sieve surface is rich in silanol and aluminol hydroxyl groups, which can form covalent bonds with the amino groups in the coupling structure of the nanoporous layer, further facilitating the loading of the molecular sieve.

[0093] In some possible implementations, the average particle size of the molecular sieve is 200 nm to 300 nm. For example, the average particle size of the molecular sieve can be any typical but non-limiting point value or a range between any two points, such as 200 nm, 210 nm, 220 nm, 230 nm, 240 nm, 250 nm, 260 nm, 270 nm, 280 nm, 290 nm, and 300 nm. In this case, a reasonable particle size range for the molecular sieve is set to 200 nm to 300 nm. This size is suitable for loading processes such as vacuum impregnation, avoiding clogging of the nanopore layer channels, while providing sufficient surface acidic sites to catalyze the release of flavor molecules. Simultaneously, in conjunction with its highly hydrophobic properties, it ensures effective confinement of sweeteners and flavors.

[0094] In some possible implementations, the average pore size of the molecular sieve is 0.5 nm to 2 nm; for example, the average pore size can be any typical but non-limiting point value or an interval between any two point values, such as 0.5 nm, 0.8 nm, 1.0 nm, 1.2 nm, 1.5 nm, 1.8 nm, and 2.0 nm. In this case, the tiny pores in the molecular sieve can selectively confine small molecules.

[0095] In some possible implementations, the loading of molecular sieves in the storage material is 2wt% to 3wt%. Exemplary examples include any typical but non-limiting point value or a range between any two points, such as 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, and 3.0wt%. In this case, the molecular sieve loading will not clog the fiber gaps or nanopores of the composite nanoporous layer of the storage substrate, maintaining the capillary action and liquid conduction velocity of the storage material. Simultaneously, an appropriate amount of molecular sieve allows its surface acidic sites to better adsorb flavor molecules, enhancing the aroma complexity. Its pore structure enables better release control of small-molecule sweeteners, enriching the aerosol's flavor profile and maintaining a balance between sweetness and aroma.

[0096] For example, the loading of the molecular sieve in the storage material in the embodiments of this application can be calculated by measuring the change in the total mass of the storage material before and after the molecular sieve is loaded.

[0097] In some possible implementations, the loading of quantum dots in the reservoir material is 0.5 wt% to 1.5 wt%. Exemplary examples include typical but not limiting values ​​such as 0.5 wt%, 0.8 wt%, 0.9 wt%, 1.0 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, and 1.5 wt%, or any range between any two values. In this case, the quantum dot loading ensures sufficient anchoring of aroma molecules, ensuring a sustained-release effect while avoiding both excessively slow and excessively fast release rates. Furthermore, it prevents quantum dot aggregation and blockage of the pores or fiber gaps in the nanoporous layer, ensuring the permeation rate of the aerosol-forming matrix and the flexibility and long-term stability of the reservoir substrate.

[0098] Among some possible implementations, quantum dots include at least one of nitrogen-doped carbon quantum dots, chitosan-cyclodextrin composite quantum dots, metal-organic framework modified quantum dots, and citric acid-polyetherimide quantum dots. These quantum dots can all further delay the release of aroma molecules containing benzene rings or conjugated double bonds through π-π conjugation.

[0099] In some possible implementations, the nitrogen doping mass percentage in nitrogen-doped carbon quantum dots is 6% to 9%. Exemplary values ​​could be any typical but non-limiting point value, such as 6%, 7%, 8%, or 9%, or any range between two points. In this case, the core advantages of nitrogen-doped carbon quantum dots are: the introduction of nitrogen atoms (CN, C=N bonds) significantly enhances surface polarity, strengthens affinity with polar aerosol matrices, and promotes liquid conductivity; pyridine nitrogen forms a stable bond with the liquid storage substrate and nanoporous layer components through π-π stacking, preventing quantum dot migration; graphitic nitrogen and carboxylate ions synergistically form a weakly acidic microenvironment, which can catalyze the controllable release of ester flavor molecules, maintaining aroma layers; and the surface defect sites formed by nitrogen doping preferentially adsorb large-molecule flavors, inhibiting the migration of small sweetener molecules. The optimal nitrogen content range is 6% to 9% (mass percentage). Too high a content (>9%) will lead to a decrease in the crystallinity of quantum dots and an increase in the tendency to agglomerate, affecting the uniformity of the nanoporous layer; too low a content (<6%) will result in insufficient surface polarity, and reduced liquid conduction efficiency and anchoring stability.

[0100] This application's embodiments achieve graded controlled release of sweeteners and aroma molecules through the synergistic effect of multiple materials (size sieving + chemical anchoring): molecular sieves selectively adsorb and delay sweetener release through size sieving and surface acidic sites; nanopores in the nanoporous layer preferentially allow small aroma molecules to pass through, and the permeation rate is regulated by surface chemical modification; while quantum dots further delay their release by anchoring aroma molecules containing benzene rings or conjugated double bonds through π-π conjugation. This graded controlled release mechanism achieves controllable release order based on differences in molecular size, binding energy (the anchoring force of quantum dots to aroma molecules is stronger than that of molecular sieves to sweeteners), and environmental responsiveness (such as the difference in the destructive effect of temperature increases on different binding forces).

[0101] In some embodiments, the shape of the liquid storage material can be flexibly adjusted, thereby improving the application flexibility of the liquid storage material. For example, the shape of the liquid storage material is shown in the attached figure. Figure 1 As shown. The liquid storage material in this embodiment of the application can control the release of large-molecule sweeteners in the aerosol generation matrix through electrostatic repulsion within the nanoporous layer and the confinement effect of the supported molecular sieves, resulting in a moderate sweetness in the aerosol and reducing the interference of sweetener release on flavor release. Meanwhile, small-molecule flavors can smoothly pass through the pores within the nanoporous layer, and through quantum dot adsorption, achieve an orderly and sustained release effect.

[0102] The liquid storage material described in the above embodiments of this application can be prepared by the methods described in the following embodiments.

[0103] Secondly, embodiments of this application provide a method for preparing a liquid storage material, as shown in the attached figure. Figure 2 As shown, it includes the following steps: S10. Obtain a porous liquid storage substrate; S20. An amphiphilic polymer layer is prepared on the porous framework surface of the liquid storage substrate; the amphiphilic polymer layer includes a hydrophobic polymer layer and a hydrophilic polymer layer stacked together. S30. A nanoporous layer is prepared on the surface of the amphiphilic polymer layer; S40. Molecular sieves and quantum dots are loaded onto the surface of the nanoporous layer to obtain a liquid storage material.

[0104] The method for preparing the storage material in this application involves preparing an amphiphilic polymer layer on the surface of the storage substrate. Grafting the amphiphilic polymer layer creates a stable gradient wettability interface on the substrate surface, enabling selective penetration of molecules of different polarities and sizes. A nanoporous layer is prepared on the surface of the amphiphilic polymer layer, which facilitates subsequent loading of molecular sieves and quantum dots, and allows for the selective adsorption of sweeteners and flavorings of different molecular weights, thus delaying their migration and achieving sustained release of sweetness and aroma. Molecular sieves and quantum dots are loaded onto the surface of the nanoporous layer. The selective adsorption of molecular sieves adsorbs sweetener molecules, regulating their migration and release; the π-π conjugation of quantum dots anchors terpene aroma molecules, enhancing aroma anchoring. This ensures that the prepared storage material can guarantee the liquid conduction rate to the aerosol-generating matrix while also enabling differential transport of molecules of different polarities within the aerosol-generating matrix, achieving graded controlled release of aroma and sweetness.

[0105] In step S10 above: a porous liquid storage substrate is obtained.

[0106] In some embodiments, the materials of the liquid storage substrate include, but are not limited to, polyethylene terephthalate (PET), polyethylene terephthalate (PET) / polyamide (PA) blends, etc., with a porosity of 90%~96% and a density of 0.05 g / cm³. 3 ~0.1g / cm 3 Its high porosity is beneficial for the storage and transport of aerosol generation matrix.

[0107] In some embodiments, the material of the liquid storage substrate includes a core-sheath structure of polyethylene terephthalate (PET) / polyamide (PA), wherein polyethylene terephthalate (PET) serves as the sheath of the fiber material and polyamide (PA) serves as the core of the fiber material.

[0108] In step S20 above: In some possible implementations, the steps for preparing the amphiphilic polymer layer include: S21. After plasma activation treatment of the liquid storage substrate, an activated substrate is obtained. Plasma activation treatment removes surface contaminants and generates hydroxyl (-OH) and carboxyl (-COOH) active sites, enhancing surface reactivity. This ensures effective utilization of the active sites, forming a stable gradient wettability interface and enabling selective penetration of polar molecules.

[0109] In some possible implementations, the plasma activation treatment power is 40W~60W, the duration is 90s~150s, and the temperature is 30℃~50℃. Cold plasma activation treatment is performed at a low temperature of 30℃~50℃ to avoid substrate deformation caused by high temperatures. The plasma activation power and duration ensure both effective activation of the substrate, ensuring the generation of sufficient hydroxyl (-OH) and carboxyl (-COOH) active sites, and avoid over-etching the substrate.

[0110] For example, the power of the plasma activation treatment can be any typical but non-limiting point value or a range between any two points, such as 40W, 45W, 50W, 55W, 60W; the duration can be any typical but non-limiting point value or a range between any two points, such as 90s, 100s, 110s, 120s, 130s, 140s, 150s; and the temperature can be any typical but non-limiting point value or a range between any two points, such as 30℃, 35℃, 40℃, 45℃, 50℃.

[0111] S22. The activated substrate is immersed in a solution of hydrophobic polymer monomers and subjected to a plasma hydrophobic grafting reaction to form a first hydrophobic polymer layer; In some possible implementations, the concentration of the hydrophobic polymer monomer solution is 20% to 40%; exemplaryly, it can be any typical but non-limiting point value or a range between any two points, such as 20%, 25%, 30%, 35%, or 40%. At this concentration, it is beneficial for the hydrophobic polymer monomer to crosslink the polymer, forming a first hydrophobic polymer layer.

[0112] In some possible implementations, the plasma hydrophobic grafting reaction has a power of 20W~40W and a duration of 20s~60s. Under these conditions, high-density free radicals (•OH, •COOH) are generated by bombarding the substrate surface with low-power plasma. These free radicals react with the double bonds (C=C) in the hydrophobic polymer monomers to form COC covalent bonds. Through the self-assembly of the hydrophobic polymer monomers, cross-linking polymerization forms the first hydrophobic polymer layer.

[0113] For example, the power of the plasma hydrophobic grafting reaction can be any typical but non-limiting point value or a range between any two points, such as 20W, 25W, 30W, 35W, 40W; the duration can be any typical but non-limiting point value or a range between any two points, such as 20s, 30s, 40s, 50s, 60s.

[0114] S23. Immerse the polymer in a solution of hydrophilic polymer monomers and perform a plasma hydrophilic grafting reaction to form a first hydrophilic polymer layer.

[0115] In some possible implementations, the concentration of the hydrophilic polymer monomer solution is 10% to 30%; for example, it can be any typical but non-limiting point value or a range between any two point values, such as 10%, 12%, 15%, 20%, 25%, 30%.

[0116] In some possible implementations, the plasma hydrophilic grafting reaction has a power of 10W~30W and a duration of 10s~60s. In this case, low-power plasma selectively breaks down the segments of hydrophilic polymer monomers containing active groups, exposing active groups such as -OH and -COOH. These active groups then form a hydrogen-bonded cross-linking network with the residual free radicals in the first hydrophobic polymer layer. The hydrophilic polymer monomers self-assemble and cross-link to form the first hydrophilic polymer layer. A wettability gradient is formed between the first hydrophobic polymer layer and the hydrophilic polymer layer, driving the directional transport of polar / nonpolar components in the aerosol generation matrix.

[0117] For example, the power of the plasma hydrophilic grafting reaction can be any point value or an interval between any two points, such as 10W, 15W, 20W, 25W, 30W, etc., which are typical but not limiting. The duration can be any point value or an interval between any two points, such as 10s, 20s, 30s, 40s, 50s, 60s, etc., which are typical but not limiting.

[0118] S24. On the surface of the first hydrophilic polymer layer, a second hydrophobic polymer layer and a second hydrophilic polymer layer are sequentially stacked to obtain an amphiphilic polymer layer. In this embodiment, the second hydrophobic polymer layer and the second hydrophilic polymer layer are sequentially prepared by repeating steps S22 and S23 to obtain a multilayered composite amphiphilic polymer layer. Through the synergistic effect of the multilayered hydrophilic and hydrophobic polymer layers, an alternating layered structure is formed, creating a better wettability gradient and better driving the directional transport of polar / non-polar components in the aerosol generation matrix.

[0119] In this application, the amphiphilic polymer layer is an alternating layered structure, meaning that alternating layers of hydrophobic and hydrophilic polymers form a periodic layered arrangement resembling "hydrophobic-hydrophilic-hydrophobic-hydrophilic" on the substrate surface. This creates a gradient wettability (referring to a continuous or stepwise change in wettability along the material thickness direction), achieved through the layered stacking of materials with different wettability (hydrophobic + hydrophilic). While each layer may not be a continuous film but rather a polymer layer grafted onto the fiber surface, it can be assumed that each grafting represents one layer. The ultra-low surface energy and rigid structure of the hydrophobic polymer layer can regulate the diffusion of macromolecules such as glycerol in the aerosol-generating matrix; the hydrophilic polymer layer, after absorbing water and swelling, constructs hydrophilic channels, promoting the rapid transport of small molecules such as propylene glycol. The alternating grafting of these two layers forms a microphase-separated layered structure. This "microphase separation" is composed of alternating grafted amphiphilic polymer layers and can also be understood as layered phase separation. This design, through the construction of a biomimetic layered heterostructure, improves liquid conductivity while utilizing interfacial chemical potential differences to achieve the orderly release of fragrance molecules, thus solving the aroma mixing problem caused by traditional high liquid conductivity materials. The alternation of hydrophobic and hydrophilic polymer layers in the amphiphilic polymer layer ensures the porosity of the liquid storage material and the graded release control of fragrances and sweeteners.

[0120] In step S30 above: In some possible implementations, the nanoporous layer comprises a porous nanoframework material and inorganic nanoparticles bonded to the porous nanoframework material. The steps for preparing the nanoporous layer include: S31. Inorganic nanoparticle precursor materials and porous nanoframework materials are dissolved in a solvent and subjected to hydrolysis and condensation reactions to obtain a sol. In this case, the porous nanoframework material serves as a biological template to guide the hydrolysis and condensation of the precursor to form a nanoporous layer. The porous nanoframework material achieves stable dispersion through dynamic hydrogen bonding between surface hydroxyl groups and / or electrostatic repulsion of negatively charged surfaces, thereby forming a porous nanoframework material with uniform pore size distribution (three-dimensional network framework). Meanwhile, the precursor material forms amorphous inorganic nanoparticles through hydrolysis and condensation reactions, resulting in a stable sol-gel system.

[0121] In some possible implementations, the precursor material includes at least one of tetraethyl orthosilicate, methyltrimethoxysilane, sodium silicate, tetramethylsilane, bio-derived silicon source, organic-inorganic hybrid precursor, and 3-aminopropyltriethoxysilane; these precursor materials form amorphous inorganic nanoparticles through hydrolysis and condensation reactions.

[0122] In some possible implementations, the mass ratio of precursor material to porous nanoframework material is (4~6):1; exemplary values ​​could be any typical but non-limiting point value such as 4:1, 5:1, or 6:1, or a range between any two point values. At this ratio, the precursor material can fully encapsulate the porous nanoframework material to form a uniform core-shell structure, and the porous nanoframework material forms a three-dimensional network porous structure during subsequent processing. This ratio of precursor material to porous nanoframework material can reduce the activation energy of the condensation reaction and promote the formation of the three-dimensional network.

[0123] In some possible implementations, the pH value of the mixed solution of the precursor material, the porous nanoframework material, and the solvent is 4–5. Exemplarily, the pH value can be any typical but non-limiting point value or a range between any two points, such as 4, 4.1, 4.2, 4.3, 4.5, 4.6, 4.8, 4.9, 5.0. Under acidic conditions, the precursor material hydrolyzes, promoting the formation of linear oligomers.

[0124] In some embodiments, cellulose nanocrystals (CNCs) are stably dispersed in an ethanol / water system through dynamic hydrogen bonding between surface hydroxyl groups and electrostatic repulsion of negatively charged surfaces (carboxyl groups ionize at pH 4-5), forming a three-dimensional network framework with a pore size distribution of 20-100 nm. SiO2 precursors (such as the hydrolysis product of tetraethyl orthosilicate (TEOS)) are distributed within the CNC network in various ways: some SiO2 forms "rigid nodes" on the CNC surface through Si-OC bonds; some SiO2 nanoparticles are embedded in the pores of the CNC network to form a "filling reinforcement" structure, or grow in situ on the CNC surface to form a "core-shell" structure (CNC as the core, SiO2 as the shell); furthermore, incompletely condensed oligomeric siloxanes dispersed in the sol can further participate in the polycondensation reaction. This composite structure combines the skeletal support of CNCs with the functional enhancement properties of SiO2.

[0125] S32. A sol is deposited onto the surface of the amphiphilic polymer layer to form a nanoporous layer. The porous structure of the nanoporous layer facilitates the efficient loading and immobilization of subsequent molecular sieves and quantum dots.

[0126] S33. The surface of the nanoporous layer is treated with a coupling agent solution followed by annealing to form a coupling structure within the nanoporous layer. This coupling structure further enhances the bonding stability between the inorganic nanoparticles and the porous nanoframework material in the nanoporous layer, and also strengthens the bond strength between the nanoporous layer and the substrate. It also facilitates the subsequent loading of molecular sieves and quantum dots. Annealing promotes the dehydration and condensation of unreacted groups, increases covalent bond density, and enables the formation of Si-O-Si coupling network structures between coupling agent molecules, thereby improving the mechanical stability of the nanoporous layer.

[0127] In some possible implementations, the coupling agent includes at least one of 3-aminopropyltrimethoxysilane (APTES), N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (AEAPTMS), mercaptosilanes (such as MPTMS), epoxysilanes (such as GPTMS), titanate coupling agents (such as isopropyltris(dioctylpyrophosphate)titanate), and polydopamine (PDA). These coupling agents are firmly bound to the nanoporous layer through a dual mechanism of chemical bonding and physical adsorption, enhancing the bonding stability between inorganic nanoparticles and porous nanoframework materials in the nanoporous layer.

[0128] In some possible implementations, the coupling agent includes 3-aminopropyltrimethoxysilane (APTES). APTES is firmly bound to the SiO2 / CNC nanoporous layer through a dual mechanism of chemical bonding and physical adsorption: In terms of chemical bonding, APTES hydrolyzes in ethanol solution to generate silanol groups, which condense with hydroxyl groups on the SiO2 surface in the nanoporous layer to form Si-O-Si covalent bonds, anchoring the SiO2 nanoparticles to the surface. Simultaneously, the silanol groups can also condense with hydroxyl groups on the CNC surface to form Si-OC covalent bonds, enhancing the interfacial bonding with the CNC network. In terms of physical adsorption, the amino groups at the ends of APTES bind to the hydroxyl or carboxyl groups of the CNC through hydrogen bonding, and under acidic conditions (pH=4~5), form electrostatic adsorption with the negatively charged CNC surface. In addition, annealing at 80℃ can promote the dehydration condensation of unreacted silanol groups, enhance the covalent bond density, and form a Si-O-Si network between APTES molecules, thereby improving the mechanical stability of the nanoporous layer.

[0129] In some possible implementations, the concentration of the coupling agent solution is 2% to 4%; exemplaryly, it can be any typical but non-limiting point value or a range between any two points, such as 2%, 2.5%, 3%, 3.5%, and 4%. In this case, the concentration of the coupling agent can effectively enhance the bonding strength between the nanoporous layer and the substrate. In some possible implementations, the loading of coupling agent in the nanoporous layer is typically 0.5 wt% to 3 wt% relative to the total mass of the nanoporous layer. When the loading exceeds 3 wt%, excessive coupling agent undergoes excessive condensation on the surface, forming dense siloxanes, leading to blockage of 2-5 nm nanopores. This reduces the selective penetration ability of fragrance molecules and decreases the liquid conduction rate. Furthermore, the coupling agent self-polymerizes to form oligomers instead of bonding with the substrate, resulting in decreased adhesion between the nanoporous layer and the substrate, making it prone to cracking or peeling. Unreacted coupling agent residues lead to a lower thermal degradation temperature, and the release of volatile substances during annealing creates microcracks, making the nanoporous layer prone to aging during long-term use.

[0130] In some possible implementations, the annealing temperature is 70℃~90℃, and the duration is 0.5h~2h. In this case, annealing promotes the dehydration and condensation of unreacted groups, enhances covalent bond density, and facilitates the formation of Si-O-Si coupling network structures between coupling agent molecules, thereby improving the mechanical stability of the nanoporous layer. Annealing drives away residual water in the nanoporous layer, reducing competitive adsorption between the coupling agent and water, and increasing the effective concentration of the coupling agent at the interface. Annealing causes thermal shrinkage of the nanoporous layer, increasing its density. Internal stresses generated during nanoporous layer deposition (such as sol drying shrinkage stress) are released through annealing, preventing microcrack propagation. The difference in thermal expansion coefficients between the nanoporous layer and the substrate is reconciled under a gradually varying temperature field, reducing the risk of interfacial delamination.

[0131] For example, the annealing temperature can be any typical but non-limiting point value or an interval between any two points, such as 70℃, 75℃, 80℃, 85℃, 90℃, etc., and the duration can be any typical but non-limiting point value or an interval between any two points, such as 0.5h, 1h, 1.5h, 2h, etc.

[0132] In step S40 above: molecular sieves and quantum dots are loaded in the nanoporous layer. Molecular sieves regulate the sustained release of sweeteners, and quantum dots enhance aroma anchoring, thereby achieving graded controlled release of aroma and sweetness.

[0133] In some possible implementations, the loading of molecular sieves includes the steps of: immersing a substrate with a nanoporous layer on its surface in a dispersion of molecular sieves, and then loading the molecular sieves onto the surface of the nanoporous layer through vacuum impregnation. The bonding mechanism between the molecular sieves and the surface of the nanoporous layer is mainly physical adsorption such as hydrogen bonding, and the molecular sieves achieve bonding through surface pore anchoring (embedding themselves in micron-sized pores or fiber gaps on the surface of the nanoporous layer).

[0134] In some possible implementations, the vacuum level of vacuum impregnation is no higher than 10. -3 Pa, with a duration of 1h to 3h; under these conditions, it is beneficial for molecular sieves to be loaded into the nanoporous layer.

[0135] In some possible implementations, quantum dot loading includes the steps of: immersing a substrate with a nanoporous layer on its surface in a dispersion of quantum dots; and loading the quantum dots onto the surface of the nanoporous layer through conjugation. Carbon quantum dots conjugate with aromatic ring structures in the nanoporous layer, forming π-π stacking interactions. Additionally, amino groups anchored by coupling agents can form n-π conjugations with the π-system of quantum dots via lone pair electrons, while hydroxyl groups in the nanoporous layer may assist in fixing the quantum dots through hydrogen bonds. The loaded quantum dots further delay the release of aroma molecules containing benzene rings or conjugated double bonds through π-π conjugation.

[0136] In some possible implementations, the preparation of a quantum dot dispersion includes the following steps: hydrothermal reaction of citric acid and urea to obtain nitrogen-doped carbon quantum dots; ultrasonic dispersion of the nitrogen-doped carbon quantum dots in water to obtain a quantum dot dispersion. Nitrogen-doped carbon quantum dots (N-CQDs) significantly enhance surface polarity by introducing nitrogen atoms (CN, C=N bonds), strengthening their affinity for polar aerosol matrices and promoting liquid conductivity; pyridine nitrogen forms a stable bond with the liquid storage substrate and nanoporous layer components through π-π stacking, preventing quantum dot migration; graphitic nitrogen and carboxylate ions synergistically form a weakly acidic microenvironment, which can catalyze the controllable release of ester flavor molecules, maintaining aroma layers; the surface defect sites formed by nitrogen doping preferentially adsorb large-molecule flavors, inhibiting the migration of small sweetener molecules.

[0137] In some possible implementations, the hydrothermal reaction temperature is 170℃~200℃ and the duration is 4h~8h; under these hydrothermal conditions, the reaction of citric acid and urea is favorable to generate nitrogen-doped carbon quantum dots.

[0138] For example, the temperature of the hydrothermal reaction can be any typical but non-limiting point value or a range between any two points, such as 170℃, 180℃, 190℃, 200℃, etc., and the duration can be any typical but non-limiting point value or a range between any two points, such as 4h, 5h, 6h, 7h, 8h, etc.

[0139] In some possible implementations, the nitrogen content in nitrogen-doped carbon quantum dots is 6% to 9% by mass; exemplary values ​​could be any typical but non-limiting point value such as 6%, 7%, 8%, or 9%, or any range between two point values. In this case, quantum dot aggregation is avoided, ensuring the liquid conductivity and anchoring stability of the storage material.

[0140] In some possible implementations, the average particle size of nitrogen-doped carbon quantum dots is 3 nm to 5 nm. For example, it can be any typical but non-limiting point value such as 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, or a range between any two point values.

[0141] In some embodiments, molecular sieves are loaded onto the surface of the nanoporous layer before quantum dots are loaded. First, larger molecular sieve particles are loaded onto the surface of the nanoporous layer, followed by smaller quantum dots. The smaller quantum dots can then be further loaded into the gaps between the larger molecular sieve particles. This matching of large and small particles improves loading efficiency, creates a multi-level loading gradient, and promotes more uniform loading.

[0142] In some embodiments, the preparation method of the reservoir material includes the following steps: First, the surface of the reservoir substrate is treated with plasma at low temperature to activate the fiber surface and generate a large number of hydroxyl and carboxyl active sites. Then, hydrophobic polymers such as perfluorohexyl ethyl acrylate (PFHEA) and hydrophilic polymers such as polyethylene glycol methacrylate (PEGMA) are grafted alternately (alternating to avoid monomer competition leading to structural inhomogeneity and to ensure effective utilization of active sites). The hydrophobic polymers act as hydrophobic agents, forming hydrophobic regions (contact angle approximately 110°) to regulate the diffusion of macromolecules such as glycerol; the hydrophilic polymers act as hydrophilic agents, forming hydrophilic channels (contact angle approximately 35°) to promote the rapid transport of small molecules such as propylene glycol. Through the amphiphilic polymer layer with both hydrophilic and hydrophobic regions, a stable gradient wettability interface is formed in the reservoir substrate, enabling selective penetration of molecules of different polarities and sizes in the aerosol generation matrix. Then, a nanoporous layer is deposited on the surface of the storage substrate using the sol-gel method. An anchoring agent is used to delay the migration of sweeteners. Furthermore, the different pore sizes formed in the nanoporous layer selectively adsorb sweeteners and flavorings of varying molecular weights, achieving a sustained release of sweetness and aroma. Next, molecular sieves are loaded using a vacuum impregnation method, utilizing the selective adsorption properties of the sieves to adsorb sweetener molecules. Quantum dots are loaded into the storage substrate, using π-π conjugation to anchor terpene aroma molecules. By regulating the sustained release of sweeteners through molecular sieves and enhancing aroma anchoring through quantum dots, a graded controlled release of aroma and sweetness is achieved.

[0143] Thirdly, embodiments of this application provide a heating module, including the above-described liquid storage material and / or the liquid storage material prepared by the above method.

[0144] The heating module of this application embodiment includes the aforementioned liquid storage material. Through multi-level modification including a surface amphiphilic polymer layer, a nanoporous layer, molecular sieves, and quantum dots, it can ensure both the liquid conduction rate of the liquid storage material to the aerosol generation matrix and the differential transport of molecules of different polarities in the aerosol generation matrix. This enables the heating module to achieve graded controlled release of aroma and sweetness, overcoming the contradiction between the liquid conduction rate of the liquid storage material and the fidelity of sweetness and aroma in traditional heating modules.

[0145] Fourthly, embodiments of this application provide an aerosol generating device, including a power supply assembly and the aforementioned heating module.

[0146] The aerosol generator in this embodiment includes a power supply component and the aforementioned heating module. This heating module enables graded controlled release of aroma and sweetness, overcoming the contradiction between the liquid conduction rate of the storage material and the fidelity of sweetness and aroma in traditional heating modules. Therefore, it improves the user experience of the aerosol generator.

[0147] To enable those skilled in the art to clearly understand the above-described implementation details and operations, and to highlight the significant improvements in the performance of the liquid storage material, its preparation method, heating module, and aerosol generating device in the embodiments of this application, the following examples illustrate the above technical solutions.

[0148] Example 1 A liquid storage material, the preparation of which includes the following steps: 1. The liquid storage substrate is made of polyethylene terephthalate (PET) / polyamide (PA) composite fiber with a core-sheath structure, forming a porous structure. The outer layer of the composite fiber is PET, and the core layer is PA.

[0149] 2. Pretreatment of the reservoir substrate: The reservoir substrate is treated with a low-temperature plasma (50W power, 120 seconds) using an argon / oxygen mixed gas (volume ratio 3:1) to remove surface contaminants and generate hydroxyl (-OH) and carboxyl (-COOH) active sites, thereby enhancing surface reactivity. The reaction in this step is as follows: PET(-O-C6H4-CO-O-CH2-CH2-)+O• / O2 + →PET(-OH)+PET(-COOH)+CO2↑.

[0150] 3. Surface grafting of amphiphilic polymer layers to construct a gradient wettability interface: 3-1. Dissolve polyperfluorohexyl ethyl acrylate (PFHEA) monomer in anhydrous ethanol (concentration 30%), impregnate the fibers in the pretreated storage substrate, and perform plasma-induced grafting (power 30W, time 30 seconds) in an inert gas (such as nitrogen) environment. Clean the unreacted monomer, dry and cure to obtain the first hydrophobic polymer layer.

[0151] 3-2. Then, the mixture is alternately impregnated with a polyethylene glycol methacrylate (PEGMA) monomer solution (concentration 20%), subjected to secondary plasma treatment (power 20W, time 20 seconds), and dried and cured to obtain the first hydrophilic polymer layer, forming an alternating layered structure.

[0152] 3-3. Repeat steps 3-1 and 3-2 to form a 35nm microphase-separated structure through alternating grafting, obtaining an amphiphilic polymer layer to achieve selective penetration of polar molecules. The PFHEA grafting amount in the amphiphilic polymer layer is 1.7 μg / cm³. 2 (Hydrophobicity dominant); PEGMA grafting amount was 2.3 μg / cm³. 2 (Water-friendly dominant).

[0153] 4. Preparation of nanoporous layer (delaying sweetener migration through electrostatic repulsion, constructing 2-5nm nanopores for selective adsorption of macromolecular flavor components): (1) Sol preparation: Using tetraethyl orthosilicate (TEOS) as a precursor, TEOS and cellulose nanocrystals (CNC) were mixed at a mass ratio of 5:1, and hydrolysis was carried out by adding ethanol / water (pH=4~5). The sol was aged for 24 hours to ensure complete hydrolysis-condensation.

[0154] The hydrolysis reaction equation is: Si(OC2H5)4 + 4H2O → Si(OH)4 + 4C2H5OH; The polycondensation reaction equation is: Si(OH)4 → SiO2·nH2O (silicon-oxygen network); The composite equation for cellulose nanocrystals is: SiO2 + CNC-OH → SiO2…HO-CNC (hydrogen bond complex).

[0155] (2) Deposition of nanoporous layer: Using the sol prepared in (1), a 300 nm thick SiO2 / CNC nanoporous layer is formed on the surface of the reservoir substrate grafted with amphiphilic polymer by dip-coating or spin-coating. The nanoporous layer includes three levels of pore characteristics: primary pores: macropores of 50~200 nm formed by the gaps between CNC networks; secondary pores: mesopores of 2~5 nm formed by the accumulation of SiO2 nanoparticles; tertiary pores: micropores (approximately 0.5~2 nm) inside the CNC crystal.

[0156] (3) Coupling agent anchoring: The surface of the nanoporous layer of the reservoir substrate with the SiO2 / CNC nanoporous layer formed was treated with ethanol solution of 3-aminopropyltriethoxysilane (APTES (concentration 2%)) and annealed at 80°C for 1 hour to enhance the bonding force between the nanoporous layer and the substrate. The reaction of the coupling agent includes the following process: Si-(CH2)3-NH2+3H2O→(HO)3Si-(CH2)3-NH2+3C2H5OH; Si-OH (APTES)+HO-Si≡ (SiO2)→Si-O-Si≡+H2O; Si-OH (APTES)+HO-CNC→Si-O-CNC+H2O.

[0157] 5. ZSM-5 molecular sieve loading (using 0.55nm pore size to selectively confine sweetener molecules (molecular weight >150Da), and surface acidic sites to catalyze the orderly release of ester flavor molecules): ZSM-5 molecular sieve (silicon-to-aluminum ratio 200:1) was dispersed in ethanol and sonicated for 30 minutes. The nanoporous layer sample of the liquid storage substrate was placed in a vacuum impregnation bath and evacuated to 10°C. -3 Pa, soak for 2 hours, then dry at 60°C.

[0158] 6. Synthesis of quantum dot materials: Nitrogen-doped carbon quantum dots (N-CQDs) with a particle size of 3nm~5nm (nitrogen content 8%) were prepared by hydrothermal reaction of citric acid and urea (180℃, 6 hours) for later use. The reaction formula for this step is as follows: 3C6H8O7 + 5CO(NH2)2 → C 48 N5H 35 O 27 (N-CQDs)+15H2O↑+6CO2↑.

[0159] 7. Nitrogen-doped carbon quantum dots (N-CQDs) modification: The N-CQDs prepared in step 6 are dispersed in deionized water, ultrasonically treated for 30 minutes, and then impregnated with a liquid storage substrate loaded with ZSM-5 molecular sieve. The substrate is anchored to the surface through π-π conjugation and dried and cured at 60°C to obtain the liquid storage material.

[0160] Comparative Example 1 A liquid storage material, wherein the polyethylene terephthalate (PET) / polyamide (PA) material with the core-shell structure in Example 1 is used as the liquid storage material, wherein the skin layer is PET and the core layer is PA.

[0161] Comparative Example 2 A liquid storage material, the preparation steps of which differ from those of Example 1 are: step 5 is not performed.

[0162] Comparative Example 3 A liquid storage material, the preparation steps of which differ from those of Example 1 are: steps 6 and 7 are not performed.

[0163] To verify the progressiveness of the embodiments of this application, the following performance tests were performed on the above embodiments and comparative examples: 1. Through user testing, the aroma recognition level is divided into several levels: the characteristic aroma is not obvious, the characteristic aroma is average, and the characteristic aroma is obvious; 2. Through user testing, the aroma fullness is divided into several levels: weak aroma with unclear layers, average aroma with unclear layers, strong aroma with unclear layers, and full aroma with rich and balanced layers. 3. Through user testing, the sweetness test is divided into several levels: no sweetness, too sweet, weak sweetness, strong sweetness, and moderate sweetness; 4. The aftertaste (lingering aroma / sweetness) is divided into several levels based on the test: no aftertaste, weak aftertaste, average aftertaste, strong aftertaste, and pleasant aftertaste.

[0164] The test results are shown in Table 1 below:

[0165] The test results above show that, compared to Comparative Example 1 (unmodified storage substrate), Comparative Example 2 (storage material without molecular sieve loading), and Comparative Example 3 (storage material without quantum dots loading), the storage material prepared in this application embodiment, through multi-level modification of the porous framework surface of the storage substrate, forms a wettability gradient on the surface of the storage substrate. The loaded molecular sieve ZSM-5 and quantum dots N-CQDs can achieve graded controlled release of aroma and sweetness, which not only increases the recognition of characteristic aromas but also increases the fullness of aroma, making the layers richer and more balanced. The electrostatic repulsion within the nanoporous layer and the synergistic effect of molecular sieve ZSM-5 have a certain regulatory effect on sweetness, making the sweetness moderate and the release of fragrance unaffected by sweeteners. At the same time, the controlled and sustained release of fragrance by quantum dots N-CQDs and cellulose nanocrystals CNC in the nanoporous layer makes the aftertaste (lingering aroma) more comfortable and lasting.

[0166] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A liquid storage material, characterized in that, The invention comprises a porous liquid storage substrate, an amphiphilic polymer layer grafted onto the porous framework surface of the liquid storage substrate, a nanoporous layer bonded to the surface of the amphiphilic polymer layer facing away from the liquid storage substrate, and molecular sieves and quantum dots loaded on the surface of the nanoporous layer facing away from the amphiphilic polymer layer; the molecular sieves can selectively adsorb sweetener molecules and regulate the migration and release of sweeteners; the quantum dots can anchor terpene aroma molecules through π-π conjugation. Wherein, along the direction from the liquid storage substrate to the amphiphilic polymer layer, the amphiphilic polymer layer includes a plurality of alternating hydrophobic polymer layers and hydrophilic polymer layers; one of the hydrophobic polymer layers is attached to the porous skeleton surface of the liquid storage substrate; The nanoporous layer includes a porous nanoframework material with a three-dimensional network skeleton formed by nanofiber material and inorganic nanoparticles loaded on the porous nanoframework material; the inorganic nanoparticles are stacked to form a nanoporous structure; the nanoporous layer has macropores formed by the three-dimensional network skeleton, mesopores formed by the stacking of the inorganic nanoparticles, and micropores inside the crystal of the nanofiber material.

2. The liquid storage material as described in claim 1, characterized in that, Along the direction from the liquid storage substrate to the amphiphilic polymer layer, the amphiphilic polymer layer sequentially includes a first hydrophobic polymer layer, a first hydrophilic polymer layer, a second hydrophobic polymer layer, and a second hydrophilic polymer layer.

3. The liquid storage material as described in claim 2, characterized in that, In the amphiphilic polymer layer, the thicknesses of the first hydrophobic polymer layer and the second hydrophobic polymer layer are independently 20 nm to 30 nm; And / or, in the amphiphilic polymer layer, the thickness of the first hydrophilic polymer layer and the second hydrophilic polymer layer are independently 10 nm to 20 nm; And / or, in the amphiphilic polymer layer, the interlayer spacing between the first hydrophobic polymer layer and the first hydrophilic polymer layer, the first hydrophilic polymer layer and the second hydrophobic polymer layer, and the second hydrophobic polymer layer and the second hydrophilic polymer layer are each independently 10 nm to 50 nm.

4. The liquid storage material as described in claim 3, characterized in that, The hydrophobic polymer layer includes at least one hydrophobic polymer selected from perfluorohexyl ethyl acrylate, polydimethylsiloxane, polytetrafluoroethylene derivatives, and polydodecyl acrylate. And / or, the hydrophilic polymer layer comprises at least one hydrophilic polymer selected from polyethylene glycol methacrylate, polyvinyl alcohol, polyvinylpyrrolidone, and polyacrylic acid; And / or, in the amphiphilic polymer layer, the grafting amount of the hydrophobic polymer is 1.2 μg / cm. 2 ~2.5μg / cm 2 ; And / or, in the amphiphilic polymer layer, the grafting amount of the hydrophilic polymer is 1.8 μg / cm. 2 ~3.0μg / cm 2 ; And / or, in the amphiphilic polymer layer, the mass ratio of the grafted hydrophilic polymer to the hydrophobic polymer is 1:(1~1.5).

5. The liquid storage material according to any one of claims 1 to 4, characterized in that, The thickness of the nanoporous layer is 200 nm to 500 nm; And / or, the inorganic nanoparticles include at least one of SiO2 nanoparticles, TiO2 nanoparticles, and Al2O3 nanoparticles; And / or, the average particle size of the inorganic nanoparticles is 10 nm to 30 nm.

6. The liquid storage material as described in claim 5, characterized in that, The nanofiber material includes at least one of chitin nanofibers and cellulose nanocrystals; And / or, the nanoporous layer also has a coupling structure.

7. The liquid storage material as described in claim 6, characterized in that, The nanoporous layer includes macropores of 50nm to 200nm formed by the three-dimensional network framework, mesopores of 10nm to 50nm formed by the stacking of inorganic nanoparticles, and micropores of 0.5nm to 1.2nm inside the crystal of the nanofiber material. And / or, the porosity of the nanoporous layer is 60%~75%.

8. The liquid storage material according to any one of claims 1 to 4, 6 or 7, characterized in that, The molecular sieve includes at least one of ZSM-5 molecular sieve, Ga-ZSM-5 molecular sieve, and Sn-ZSM-5 molecular sieve; And / or, the average particle size of the molecular sieve is 200 nm to 300 nm; And / or, the average pore size in the molecular sieve is 0.5 nm to 2 nm; And / or, the molecular sieve is loaded into the liquid storage material at a rate of 2wt% to 3wt%.

9. The liquid storage material according to any one of claims 1 to 4, 6 or 7, characterized in that, In the liquid storage material, the loading of quantum dots is 0.5wt%~1.5wt%; And / or, the quantum dots include at least one of nitrogen-doped carbon quantum dots, chitosan-cyclodextrin composite quantum dots, metal-organic framework modified quantum dots, and citric acid-polyetherimide quantum dots.

10. The liquid storage material as described in claim 9, characterized in that, In the nitrogen-doped carbon quantum dots, the mass percentage of nitrogen doping is 6% to 9%.

11. A method for preparing a liquid storage material as described in any one of claims 1 to 10, characterized in that, Includes the following steps: Obtaining a porous liquid storage substrate; An amphiphilic polymer layer is prepared on the porous framework surface of the liquid storage substrate; the amphiphilic polymer layer comprises a hydrophobic polymer layer and a hydrophilic polymer layer stacked together. A nanoporous layer is prepared on the surface of the amphiphilic polymer layer; Molecular sieves and quantum dots are loaded onto the surface of the nanoporous layer to obtain a liquid storage material.

12. The method for preparing the liquid storage material as described in claim 11, characterized in that, The step of preparing the amphiphilic polymer layer includes: After plasma activation treatment of the liquid storage substrate, an activated substrate is obtained; The activated substrate is immersed in a solution of hydrophobic polymer monomers and subjected to a plasma hydrophobic grafting reaction to form a first hydrophobic polymer layer. The polymer is immersed in a solution of hydrophilic polymer monomers and subjected to a plasma hydrophilic grafting reaction to form a first hydrophilic polymer layer. On the surface of the first hydrophilic polymer layer, a second hydrophobic polymer layer and a second hydrophilic polymer layer are sequentially stacked to obtain the amphiphilic polymer layer.

13. The method for preparing the liquid storage material as described in claim 12, characterized in that, The plasma activation treatment has a power of 40W~60W, a duration of 90s~150s, and a temperature of 30℃~50℃. And / or, the concentration of the hydrophobic polymer monomer solution is 20%~40%; And / or, the concentration of the hydrophilic polymer monomer solution is 10%~30%; And / or, the power of the plasma hydrophobic grafting reaction is 20W~40W, and the duration is 20s~60s; And / or, the power of the plasma hydrophilic grafting reaction is 10W~30W, and the duration is 10s~60s.

14. The method for preparing the liquid storage material according to any one of claims 11 to 13, characterized in that, The nanoporous layer comprises a porous nanoframework material and inorganic nanoparticles bonded to the porous nanoframework material. The steps for preparing the nanoporous layer include: The inorganic nanoparticle precursor material and the porous nanoframework material are dissolved in a solvent and subjected to hydrolysis and condensation reactions to obtain a sol. The sol is deposited onto the surface of the amphiphilic polymer layer to form the nanoporous layer; The surface of the nanoporous layer is treated with a coupling agent solution and then annealed to form a coupling structure in the nanoporous layer.

15. The method for preparing the liquid storage material as described in claim 14, characterized in that, The precursor material includes at least one of tetraethyl orthosilicate, methyltrimethoxysilane, sodium silicate, tetramethylsilane, bio-derived silicon source, organic-inorganic hybrid precursor, and 3-aminopropyltriethoxysilane. And / or, the mass ratio of the precursor material to the porous nanoframework material is (4~6):1; And / or, the pH value of the mixed solution of the precursor material, the porous nanoframework material and the solvent is 4 to 5; And / or, the coupling agent comprises at least one of 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, mercaptosilane, epoxysilane, titanate coupling agent, and polydopamine; And / or, the concentration of the coupling agent solution is 2% to 4%; And / or, the annealing treatment is performed at a temperature of 70℃~90℃ for a duration of 0.5h~2h.

16. The method for preparing the liquid storage material according to any one of claims 11-13 or 15, characterized in that, The loading of the molecular sieve includes the following steps: immersing a substrate on which the nanoporous layer is formed on its surface in the dispersion of the molecular sieve, and loading the molecular sieve onto the surface of the nanoporous layer by vacuum impregnation. And / or, the loading of the quantum dots includes the steps of: immersing a substrate on which the nanoporous layer is formed on its surface in a dispersion of the quantum dots, wherein the quantum dots are loaded onto the surface of the nanoporous layer through conjugation.

17. The method for preparing the liquid storage material as described in claim 16, characterized in that, The vacuum degree of the vacuum impregnation is not higher than 10. -3 Pa, duration is 1h~3h; And / or, after loading the molecular sieve onto the surface of the nanoporous layer, the quantum dots are then loaded.

18. A heating module, characterized in that, This includes the liquid storage material as described in any one of claims 1 to 10 and / or the liquid storage material prepared by the method described in any one of claims 11 to 17.

19. An aerosol generating device, characterized in that, It includes a power supply assembly and a heating module as described in claim 18.

Citation Information

Patent Citations

  • Directional liquid guide composite membrane with lithium extraction function, preparation method and application

    CN114225720A

  • Inhaler system for volatile substances

    US20130047984A1

  • Hydrophilic material and method of manufacturing

    US5028332A